2009
DOI: 10.3928/01477447-20090527-14
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalist–Orthopedic Co-management of High-risk Patients Undergoing Lower Extremity Reconstruction Surgery

Abstract: The introduction of the hospitalist co-management model represents an opportunity to improve care by changing the system as it applies to a small group of patients. Eighty-six consecutive patients with multiple comorbidities were selectively enrolled in an academic medical center hospitalist-orthopedic surgery co-management patient care program. Patients were stratified by all patient refined diagnosis-related groups, severity of illness, and risk of mortality. Hospital length of stay, cost of care, in-hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…Thirty-five of the fifty-eight articles that examined average or median length of stay found that patients managed by hospitalists had significantly shorter hospital stays compared to those who received traditional models of inpatient care (60%). Five additional papers suggested similar declines (9%); however, the authors failed to disclose the statistical significance of their findings [44,60,61,77,78]. Shorter lengths of hospital stays persisted across all hospitalist practice models: Twelve (80%) of fifteen articles comparing nonacademic hospitalists to community-based physicians and eleven (61%) of eighteen articles comparing nonacademic hospitalists with traditional academic attending physicians showed shorter patient hospital stays under hospitalist care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-five of the fifty-eight articles that examined average or median length of stay found that patients managed by hospitalists had significantly shorter hospital stays compared to those who received traditional models of inpatient care (60%). Five additional papers suggested similar declines (9%); however, the authors failed to disclose the statistical significance of their findings [44,60,61,77,78]. Shorter lengths of hospital stays persisted across all hospitalist practice models: Twelve (80%) of fifteen articles comparing nonacademic hospitalists to community-based physicians and eleven (61%) of eighteen articles comparing nonacademic hospitalists with traditional academic attending physicians showed shorter patient hospital stays under hospitalist care.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies where admission and preoperative assessments were conducted by hospitalists as opposed to a member of the surgical team, mean time to surgery was reduced by 35% to 50% [62,81,82]. Along with improvements in efficiency prior to surgery, overall lengths of stay for surgical patients comanaged by hospitalists were reduced in all studies [48,77,82-84], although none demonstrated associated reductions in costs [48,77]. Last, while hospitalist teams are often argued to improve emergency department flow through active and ongoing bed management, only one evaluation to date has reported significant improvements in emergency department processing [58], but no form of risk adjustment was used in their analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Medical co-management of high-risk surgical patients by hospitalists is indeed not a new concept. Although some studies suggest such practice can lead to lower mortality and shorter hospital length of stay [26][27][28], others have shown no significant outcomes effects [29,30]. However, anesthesiologists have the advantage over hospitalists of already being familiar with the surgical issues of the patient.…”
Section: Perioperative Surgical Home Modelmentioning
confidence: 96%
“…The introduction of the hospitalist co-management model represents an opportunity to improve care. Pinzur et al (76) conducted a study investigating the outcomes of diabetic patients undergoing treatment of osteomyelitis and Charcot osteoarthropathy reconstruction after being enrolled in an academic medical center hospitalist-orthopedic surgery co-management patient care program. While the overall observed-to-expected cost of care remained virtually unchanged, the positive impact of the study model revealed an increased positive effect on the more severely affected severity of illness and risk of mortality patients.…”
Section: Treatment Strategies For Charcot Osteoarthropathy With or Wimentioning
confidence: 99%